Treatment and clinical outcomes of patients relapsing after allogeneic hematopoietic cell transplantation for myelodysplastic syndrome - Choi, Eun-Ji; Lee, Je-Hwan; Lee, Jung-Hee; Park, Han-Seung; Ko, Sun-Hye; Seol, Miee; Lee, Young-Shin; Kang, Young-Ah; Jeon, Mijin; Lee, Kyoo-Hyung (Blood research, 2018)
Although allogeneic hematopoietic cell transplantation (HCT) is the only curative treatment option for myelodysplastic syndrome (MDS), a substantial number of patients experience relapse. We reviewed the clinical outcomes of patients with MDS who relapsed after allogeneic HCT. Thirty patients who experienced relapse or progression after allogeneic HCT for MDS between July 2000 and May 2016 were included in this retrospective analysis. The median time from HCT to relapse was 6.6 (range, 0.9-136.3) months. Donor lymphocyte infusions (DLIs) were administered to four patients: one achieved complete remission (CR) and survived disease free, while three did not respond to DLI and died. Hypomethylating agents were administered to seven patients: one who had stable disease continuously received decitabine, while six died without response to treatment. Six patients received AML-like intensive chemotherapy, and three achieved CR: two underwent second HCT and one DLI. One patient receiving second HCT survived without disease, but the other two relapsed and died. Three, four, and eight patients who did not respond to intensive chemotherapy, low-dose cytarabine, and best supportive care, respectively, died. One patient who underwent second HCT following cytogenetic relapse survived disease free. Median overall survival after relapse was 4.4 months, and relapse within 6 months after HCT was associated with shorter survival. Outcomes of MDS patients relapsing after allogeneic HCT were disappointing. Some patients could be saved using DLI or second HCT.